Anti-obesity effects of galangin, a pancreatic lipase inhibitor in cafeteria diet fed female rats. (May 2013) - Kumar, Shiv; Alagawadi, K. R.
Abstract Context: Alpinia galanga Willd (Zingiberaceae) (AG) is a rhizomatous herb widely cultivated in shady regions of Malaysia, India, Indochina and Indonesia. It is used in southern India as a domestic remedy for the treatment of rheumatoid arthritis, cough, asthma, obesity, diabetes, etc. It was reported to have anti-obesity, hypoglycemic, hypolipidemic and antioxidant properties. Objective: A flavonol glycoside, galangin, was isolated from AG rhizomes. Based on its in vitro pancreatic lipase inhibitory effect, the study was further aimed to clarify whether galangin prevented obesity induced in female rats by feeding cafeteria diet (CD) for 6 weeks. Materials and methods: The in vitro pancreatic lipase inhibitory effect of galangin was determined by measuring the release of oleic acid from triolein. For in vivo experiments, female albino rats were fed CD with or without 50 mg/kg galangin for 6 weeks. Body weight and food intake was measured at weekly intervals. On day 42, serum lipids levels were estimated and then the weight of liver and parametrial adipose tissue (PAT) was determined. The liver lipid peroxidation and triglyceride (TG) content was also estimated. Results: The IC50 value of galangin for pancreatic lipase was 48.20 mg/mL. Galangin produced inhibition of increased body weight, energy intake and PAT weight induced by CD. In addition, galangin produced a significant decrease in serum lipids, liver weight, lipid peroxidation and accumulation of hepatic TGs. Conclusion: Galangin present in AG rhizomes produces anti-obesity effects in CD-fed rats; this may be mediated through its pancreatic lipase inhibitory, hypolipidemic and antioxidant activities.